Evaluating the central vein sign in paediatric-onset multiple sclerosis: A case series study. (March 2023) - Boccia, Vincenzo Daniele; Lapucci, Caterina; Cellerino, Maria; Tazza, Francesco; Rossi, Andrea; Schiavi, Simona; Mancardi, Maria Margherita; Inglese, Matilde
The central vein sign (CVS) has been proposed as a biomarker of multiple sclerosis (MS). In adult-onset MS (AOMS), 40%-threshold of CVS positive (+) lesions demonstrated high accuracy for MS diagnosis. However, CVS+ lesions' performance has not been characterized in paediatric-onset (POMS) yet. We compared the CVS contribution to MS diagnosis in 10 POMS and 12 disease-duration-matched AOMS patients. Three POMS patients did not meet the 40%-threshold, while all AOMS patients were correctly diagnosed as having MS. The high proportion of periventricular confluent lesions, excluded from the CVS assessment, seemed to impair CVS sensitivity in POMS diagnosis.